Game-Based Learning Strategies to Improve Student Motivation in Islamic History (Tarikh) Learning - Risdianatul Ilmi; Anita Puji Astutik (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Game-Based Learning Strategies to Improve Student Motivation in Islamic History (Tarikh) LearningObjective: This study aims to analyze the implementation of Game-Based Learning (GBL) strategies in enhancing student motivation in the Islamic History subject at SD Muhammadiyah 15 Surabaya. Method: The research employs a descriptive qualitative design, utilizing data collection techniques that include in-depth interviews, participatory observation, and documentation. Results: The use of GBL with Kahoot created an interactive learning environment, enhancing motivation, participation, and understanding of Islamic history. It also promoted critical thinking, problem-solving, and teamwork. Despite challenges such as limited technology and varying student abilities, GBL effectively enhanced student motivation. Conclusion: The Game-Based Learning strategy can be an innovative alternative to create more engaging, meaningful, and character-strengthening Islamic History lessons. Contribution: This study makes a significant contribution to the development of creative and impactful teaching strategies in Islamic education, thereby promoting a more interactive and values-based learning experience.INDONESIAN: Strategi Game Based Learning dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Tarikh IslamTujuan: Penelitian ini bertujuan untuk menganalisis penerapan strategi Game-Based Learning (GBL) dalam meningkatkan motivasi belajar siswa pada mata pelajaran Sejarah Islam di SD Muhammadiyah 15 Surabaya. Metode: Penelitian ini menggunakan desain kualitatif deskriptif dengan teknik pengumpulan data berupa wawancara mendalam, observasi partisipatif, dan dokumentasi. Hasil: Penggunaan GBL dengan Kahoot menciptakan lingkungan belajar yang interaktif, meningkatkan motivasi, partisipasi, dan pemahaman sejarah Islam. Model ini juga mempromosikan kemampuan berpikir kritis, pemecahan masalah, dan kerja sama. Meskipun ada tantangan seperti keterbatasan teknologi dan perbedaan kemampuan siswa, GBL efektif dalam meningkatkan motivasi siswa. Kesimpulan: Strategi Game-Based Learning dapat menjadi alternatif inovatif untuk menciptakan pembelajaran Sejarah Islam yang lebih menarik, bermakna, dan memperkuat karakter siswa. Kontribusi: Penelitian ini memberikan kontribusi dalam pengembangan strategi pembelajaran kreatif dan berdampak dalam pendidikan Islam, yang mendukung pengalaman belajar yang lebih interaktif dan berbasis nilai